THE IMPLEMENTATION OF REGIONAL AUTHORITY OF WEST JAVA PROVINCE IN THE SEA IN 2017 - afrilia, ufa anita (Advances in Social Sciences Research Journal, 2018)
The Law Number 23 of 2014 concerning Regional Government, which among others regulates the extension of authority of the Province in the maritime sector, removes the authority of the District / Municipal over the supervision of the sea and fully submitted to the Province shall come into force effective by 2017. If the original authority of the Province from 4-12 miles is now expanded to 0-12 miles. One of the implications of this policy is the increasingly difficult oversight at sea. With limited budgets and human resources, this policy is doubtful of its effectiveness, besides its application there could be the possibility of emergence of problems due to changes in authority in the marine sector whether there is an impact on the local government of the District / City and on the community. This is interesting to study, this research was conducted to see the implementation of regional authority of West Java Province in the sea in 2017. This research uses descriptive research method with qualitative approach. The results showed that with the shift of authority affairs of West Java Province in the sea, problems arose because of the limited human resources, funds, facilities and infrastructure, and the range of control that is too far so that the handling of problems that arise in exercising the authority of the province in the sea becomes longer. Based on the above exposure, it can be concluded that the implementation of regional authority of West Java Province in the sea in 2017 is not optimal. There should be a synchronization of laws and regulations that clearly regulate the authority among the implementing agencies of regional authority of West Java Province on the Sea, and on the obligation to establish zoning regulation originally based on District / City to become Province based.